PHYSIOLOGICAL AND BIOCHEMICAL BASES OF COCONUT PRODUCTION - V. RAJAGOPAL; KV KASTURIBAI; S. SHIVASHANKAR (International Coconut Community, 1991)
The relevance of the physiological arid biochemical investigations on coconut production has been amply proved. The physiological data on the seedling characters arid the equations developed for leaf area arid dry matter production proved to be valuable tools for application in the nursery selections. The experimental evidence provided by the biochemical studies opened up new vistas for utilising some of the biochemical markers related to the processes of growth arid yield in coconut palms. The rapid screening technique developed for drought tolerance offers a good scope for evaluating the germplasm collections. That the scientific management practices could substantially enhance the yield potential of root (wilt) diseased palms has been convincingly delineated.